Bendamustine plus rituximab for the treatment of Waldenström Macroglobulinemia: Patient outcomes and impact of bendamustine dosing. Issue 5 (20th March 2023) - Arulogun, Suzanne O.; Brian, Duncan; Goradia, Harshita; Cooney, Aaron; Menne, Tobias; Koo, RayMun; O'Neill, Aideen T.; Vos, Josephine M. I.; Pratt, Guy; Turner, Deborah; Marshall, Kirsty; Manos, Kate; et al.
Abstract: Bendamustine and rituximab (BR) therapy is commonly used in the treatment of Waldenström Macroglobulinemia (WM). The impact dose of Bendamustine dose on response and survival outcomes is not well‐established, and the impact of its use in different treatment settings is not clear. We aimed to report response rates and survival outcomes following BR, and clarify the impact of depth of response and bendamustine dose on survival. A total of 250 WM patients treated with BR in the frontline or relapsed settings were included in this multicenter, retrospective cohort analysis. Rates of partial response (PR) or better differed significantly between the frontline and relapsed cohorts (91.4% vs 73.9%, respectively; p  < 0.001). Depth of response impacted survival outcomes: two‐year predicted PFS rates after achieving CR/VGPR vs PR were 96% versus 82%, respectively ( p  = 0.002). Total bendamustine dose was predictive of PFS: in the frontline setting, PFS was superior in the group receiving ≥1000 mg/m 2 compared with those receiving 800–999 mg/m 2 ( p  = 0.04). In the relapsed cohort, those who received doses of <600 mg/m 2 had poorer PFS outcomes compared with those who received ≥600 mg/m 2 ( p  = 0.02). Attaining CR/VGPR following BR results in superior survival, and total bendamustine dose significantly impacts response and survival outcomes, in both frontline and relapsed settings.